Soft Robotics: Soft Somatosensitive Actuators via Embedded 3D Printing (Adv. Mater. 15/2018). Issue 15 (14th April 2018) - Truby, Ryan L.; Wehner, Michael; Grosskopf, Abigail K.; Vogt, Daniel M.; Uzel, Sebastien G. M.; Wood, Robert J.; Lewis, Jennifer A.
Abstract : Soft robotic grippers are fabricated with embedded contact pressure, inflation, and curvature sensors, as reported by Robert J. Wood, Jennifer A. Lewis, and co‐workers in article number1706383 . The creation of bioinspired soft robots with somatosensory feedback is achieved via embedded 3D printing of an ionically conductive ink within elastomeric matrices. Image credit: R. L. Truby and J. A. Lewis, Harvard University.